LIMINALITY: BLACK DEATH 700 YEARS LATER. WHAT LESSONS ARE FOR US FROM THE MEDIEVAL PANDEMIC? - BEDYŃSKI, WOJCIECH (Society Register, 2020)
Black Death, global plague of the 14th century deeply changed the society of Medieval Europe. This unexpected catastrophe killed from 30 to 60 per cent of the continent’s population remaining the most deadly of all known wars, epidemics or natural disasters up to date1. It was an impulse to a profound transformation of European society, religiosity and art that opened doors for the Renaissance. Time of the catastrophe had a clearly liminal character, well described in Boccaccio’s Decameron. It is far too early to predict the COVID-19 pandemic’s impact on the world in long-time perspective, as we know little about how and when the disaster will end, but mechanisms of the liminal period are already to be seen and can be described, so is the influence of the virus on global economy, mobility, culture. There are similarities even in human reactions – from the hostility towards Asians (pogroms of Jews as a reaction to the Black Death) to ‘corona-parties’ (similar to the plays described by Boccaccio).